Analisis Intensi Kewirausahaan Sosial Mahasiswa Program Studi Administrasi Bisnis - Ivon Sandya Sari Putri (Jurnal Riset Bisnis dan Investasi, 2018)
Social entrepreneurship is kind of business process that creates product or services which needed by society and/or environment and one of the solution to help the government to solve many kinds of social problems such as health, education, and environmental problems. The purpose of this research is to identify the degree of social entrepreneurship intention of the student in the business administration program. The questionnaire is distributed to 100 respondents. The result shows that the intention of social entrepreneurship from students in the business administration program is high (M= 3.6). The personal characteristics that support the social entrepreneur such as agreeableness, openness, conscientiousness, and extraversion has a higher degree than other personal characteristics. Those characteristics have a positive impact on the social entrepreneurship intention of students in the business administration program.